Relationship between PI3K/mTOR/RhoA pathway-regulated cytoskeletal rearrangements and phagocytic capacity of macrophages - H.R. Bao; J.L. Chen; F. Li; X.L. Zeng; X.J. Liu (Brazilian Journal of Medical and Biological Research)
The objective of this study was to investigate the relationship between PI3K/mTOR/RhoA signaling regulated cytoskeletal rearrangements and phagocytic capacity of macrophages. RAW264.7 macrophages were divided into four groups; blank control, negative control, PI3K-RNAi, and mTOR-RNAi. The cytoskeletal changes in the macrophages were observed. Furthermore, the phagocytic capacity of macrophages against Escherichia coli is reported as mean fluorescence intensity (MFI) and percent phagocytosis. Transfection yielded 82.1 and 81.5% gene-silencing efficiencies against PI3K and mTOR, respectively. The PI3K-RNAi group had lower mRNA and protein expression levels of PI3K, mTOR, and RhoA than the blank and negative control groups (Р<0.01). The mTOR-RNAi group had lower mRNA and protein levels of mTOR and RhoA than the blank and the negative control groups (Р<0.01). Macrophages in the PI3K-RNAi group exhibited stiff and inflexible morphology with short, disorganized filopodia and reduced number of stress fibers. Macrophages in the mTOR-RNAi group displayed pronounced cellular deformations with long, dense filopodia and an increased number of stress fibers. The PI3K-RNAi group exhibited lower MFI and percent phagocytosis than blank and negative control groups, whereas the mTOR-RNAi group displayed higher MFI and percent phagocytosis than the blank and negative controls (Р<0.01). Before and after transfection, the mRNA and protein levels of PI3K were both positively correlated with mTOR and RhoA (Р<0.05), but the mRNA and protein levels of mTOR were negatively correlated with those of RhoA (Р<0.05). Changes in the phagocytic capacity of macrophages were associated with cytoskeletal rearrangements and were regulated by the PI3K/mTOR/RhoA signaling pathway.